The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1038/s41598-022-17030-4
|View full text |Cite
|
Sign up to set email alerts
|

Increasing vitamin C through agronomic biofortification of arugula microgreens

Abstract: Vitamin C (Vit C) is an essential micronutrient and antioxidant for human health. Unfortunately, Vit C cannot be produced in humans and is ingested through diet while severe deficiencies can lead to scurvy. However, consumption is often inconsistent, and foods vary in Vit C concentrations. Biofortification, the practice of increasing micronutrient or mineral concentrations, can improve the nutritional quality of crops and allow for more consistent dietary levels of these nutrients. Of the three leading biofort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 48 publications
(59 reference statements)
0
14
1
Order By: Relevance
“…Increased micronutrient or mineral concentrations, or biofortification, can enhance the nutritional value of crops and enable more stable dietary levels of these nutrients [ 117 ]. The least studied method to boost vitamin C in microgreens is agronomic, particularly when ascorbic acid was added on top of the other two biofortification methods, conventional and transgenic [ 118 ]. Biofortification of vitamin C in microgreens of arugula ( Eruca sativa ‘Astro’ ) irrigated with four ascorbic acid concentrations and controlled as the supplement concentrations were grown, microgreens’ total vitamin C and ascorbic acid levels increased significantly.…”
Section: Effect Of Microgreens On Metabolic Health-promoting Applicat...mentioning
confidence: 99%
See 1 more Smart Citation
“…Increased micronutrient or mineral concentrations, or biofortification, can enhance the nutritional value of crops and enable more stable dietary levels of these nutrients [ 117 ]. The least studied method to boost vitamin C in microgreens is agronomic, particularly when ascorbic acid was added on top of the other two biofortification methods, conventional and transgenic [ 118 ]. Biofortification of vitamin C in microgreens of arugula ( Eruca sativa ‘Astro’ ) irrigated with four ascorbic acid concentrations and controlled as the supplement concentrations were grown, microgreens’ total vitamin C and ascorbic acid levels increased significantly.…”
Section: Effect Of Microgreens On Metabolic Health-promoting Applicat...mentioning
confidence: 99%
“…Biofortification of vitamin C in microgreens of arugula ( Eruca sativa ‘Astro’ ) irrigated with four ascorbic acid concentrations and controlled as the supplement concentrations were grown, microgreens’ total vitamin C and ascorbic acid levels increased significantly. In conclusion, biofortification of vitamin C in microgreens through the addition of ascorbic acid is feasible, and ingestion of these bio-fortified microgreens could assist in meeting the daily vitamin C requirements for people, hence lowering the need for additional vitamins [ 118 ]. Similarly, the possibility of iron (Fe) enrichment, biofortifying various vegetable microgreens, such as purple kohlrabi, radish, pea, and spinach microgreens, were studied to see how nutrient solutions enriched with iron chelate (1.5 and 3.0 mg/L) affected growth of the plants and mineral concentration [ 119 ].…”
Section: Effect Of Microgreens On Metabolic Health-promoting Applicat...mentioning
confidence: 99%
“…Hausen (1935) reported the possibility of biofortifying Vit C in early stages of seedling growth. Only four studies (De Souza et al, 2019;Garcia Neto et al, 2021;dos Santos et al, 2022;Kathi et al, 2022) were found in the past decade that had successfully increased Vit C content in horticultural crops. of these, there were fewer studies that document how this biofortification occurs in microgreens (Kathi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Only four studies (De Souza et al, 2019;Garcia Neto et al, 2021;dos Santos et al, 2022;Kathi et al, 2022) were found in the past decade that had successfully increased Vit C content in horticultural crops. of these, there were fewer studies that document how this biofortification occurs in microgreens (Kathi et al, 2022). In fact, Kathi et al (2022) found that arugula microgreens can be biofortified with exogenous applications of ascorbic acid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation